Cationic Antheraea pernyi Silk Fibroin-Modified Adenovirus-Mediated ING4 and IL-24 Dual Gene Coexpression Vector Suppresses the Growth of Hepatoma Carcinoma Cells - Qu J (Dove Medical Press, 2019)
Jing Qu,1 Weiwei Wang,1 Yanfei Feng,1 Longxing Niu,1 Mingzhong Li,1 Jicheng Yang,2 Yufeng Xie3 1National Engineering Laboratory for Modern Silk, College of Textile and Clothing Engineering, Soochow University, Suzhou 215123, People′s Republic of China; 2Cell and Molecular Biology Institute, College of Medicine, Soochow University, Suzhou 215123, People′s Republic of China; 3Department of Oncology, First Affiliated Hospital of Soochow University, Suzhou 215006, People′s Republic of ChinaCorrespondence: Mingzhong LiNational Engineering Laboratory for Modern Silk, College of Textile and Clothing Engineering, Soochow University, No. 199 Ren’ai Road, Suzhou 215123, People’s Republic of ChinaTel +86-512-6706-1150Fax +86-512-6724-6786Email mzli@suda.edu.cnYufeng XieDepartment of Oncology, First Affiliated Hospital of Soochow University, No.188 Shizi Road, Suzhou 215006, People′s Republic of ChinaTel +86-512-6778-0645Email sdxyf@163.comIntroduction: Cancer gene therapy requires both effective tumor suppressor genes and safe vectors that express target genes efficiently. Inhibitor of growth 4 (ING4) inhibits tumor growth via multiple pathways. Interleukin-24 (IL-24) also has tumor-suppressive activity against a broad spectrum of human cancers. Adenovirus (Ad) vectors exhibit high infection efficiency, but potential toxicity related to high doses of adenovirus has led to careful reconsideration of their use in human clinical trials. Antheraea pernyi silk fibroin (ASF) is a cytocompatible and biodegradable natural polymer, and it possesses Arg–Gly–Asp sequences exhibiting a high binding affinity and selectivity for αvβ3 and αvβ5 integrin receptors, which are overexpressed in tumor vessels and most tumor cells.Methods: In this study, an Arg-Gly-Asp peptide-modified Ad vector coexpressing ING4 and IL-24 was constructed by homologous recombination of the dual gene coexpression transfer plasmid and RGD-modified pAdEasy-1 adenoviral backbone plasmid. The cationic ASF (CASF) was prepared by modifying ASF with low-molecular-weight PEI. The negatively charged Ad vector was modified with CASF to form a CASF/Ad complex.Results: Human hepatoma carcinoma SMMC-7721 cells and normal hepatic L-02 cells were infected with the CASF/Ad complex, which showed significantly higher infection efficiency than the naked Ad. The CASF/Ad complex could effectively mediate the expression of the target gene ING4 in SMMC-7721 cells and the secretion of the target gene IL-24 from SMMC-7721 cells, thus inducing apoptosis of hepatoma carcinoma SMMC-7721 cells. The viability of SMMC-7721 and L-02 cells infected with the CASF/Ad complex was further assessed, and it was found that the growth of SMMC-7721 cells was significantly inhibited but that the growth and proliferation of L-02 cells were not affected.Conclusion: The CASF/Ad complex constructed in this study, showing improved infection efficiency and enhanced suppressive effects on human hepatoma carcinoma SMMC-7721 cells, has the potential to reduce the dose of adenovirus and still maintain high infection efficiency and tumor inhibition.Keywords: silk fibroin, adenovirus, cationic modification, hepatoma carcinoma